Exploring the impact of in-service teacher education on the professional development of elementary teachers: a case study of Odisha - Pranati Palai; Gouranga Charan Nanda (Освітній вимір)
The present study explores the professional development of elementary teachers in Odisha, considering the role of in-service teacher education (ISTE) programs. It identifies the challenges and opportunities of teaching in rural and tribal areas where educational disparities exist. Concepts like experiential and transformative learning have been considered the foundation for enhancing teaching practice. The research focuses on national initiatives under Sarva Sikhya Abhiyan and National Education Policy 2020, which have shaped the structure and effectiveness of teacher education programs. Government reports, such as the Odisha School Education Programme Authority's Annual Report and the Economic Survey of Odisha, reveal efforts to improve education in the state, especially for underserved communities. The study uses global perspectives from organisations such as UNESCO to emphasise the need for inclusive education and continuous professional development. Reviewing these sources, the study recommends strengthening ISTE programs in Odisha to enhance teacher efficacy and student learning outcomes.